MENINGKATKAN KEMAMPUAN BERBAHASA INGGRIS SISWA PESANTREN AL-HIKMAH DENGAN METODE COLLABORATIVE LEARNING - Kurniawan, Iwan (English Education: Jurnal Tadris Bahasa Inggris, 2015)
The aim of this research is to know whether the use of Collaborative Learning can increase students` English skills especially reading comprehension ability or not and whether this technique can improve students` cooperation. The subject of this research consisted of first grade Islamic Junior High School students of Pesantren Al-Hikmah Bandar Lampung. The research findings show that this method is really effective to upgrade students` reading comprehension ability and students` cooperation.